Towards balanced mechanical and electrical properties of thermoplastic vulcanizates composites via unique synergistic effects of single-walled carbon nanotubes and graphene. (22nd March 2018) - Li, Chao-Qun; Zha, Jun-Wei; Li, Zhi-Jun; Zhang, Dong-Li; Wang, Si-Jiao; Dang, Zhi-Min
Abstract: To achieve good dispersion of graphene and single-walled carbon nanotubes (SWNTs) in the nonpolar thermoplastic vulcanizate (TPV), polypropylene- graft -maleic anhydride (PP- g -MA) was compounded with graphene or SWNTs to obtain masterbatches, followed by their melt blending with TPV material. Morphological observations revealed the rather different distribution of graphene and SWNTs, which was directly related to the form of unique dual conductivity networks via the incorporation of SWNTs and graphene hybrid fillers, and also prevented the aggregation of fillers efficiently. The TPV ternary composites incorporated with hybrid fillers of graphene and SWNTs exhibited a low electrical percolation threshold of 0.37 wt % SWNTs, and higher electrical and thermal conductivity than the SWNTs incorporated binary systems at equal filler concentration. In contrast to the sharp decrease in tensile strength for TPV/SWNT composites, upon the addition of graphene into TPV/SWNT composite with a constant content of 0.5 wt% SWNTs, the increase in tensile modulus and tensile strength were 82% and 15% respectively at 2 wt % loading of graphene. Thermodynamic analysis was also applied to illustrate the different dispersion morphology of SWNTs and graphene in TPV. This study presents a new insight into the fabrication of high-performance TPV composites via the synergistic effects of hybrid fillers.